Laminated structure, cured product of resin layer in laminated structure, and electronic component having cured product
By combining the liquid epoxy resin of perovskite-type compound with solid epoxy resin in the fingerprint authentication sensor, the problem of poor dielectric constant and image formation during the development and thermal curing of the resin layer is solved, and the resin layer is realized Good adhesion and peelability with the second film improve the dielectric constant and image stability of the sensor.
Patent Information
- Application Number
- CN202380041323.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-06
- Filing Date
- 2023-05-30
- Publication Date
- 2024-12-27
AI Technical Summary
The resin layer of the insulating protective film in the existing fingerprint certified sensor is difficult to maintain high dielectric constant and good image formation during development and thermal curing, and the adhesion and peelability of the resin layer to the second film are opposite, which affects the influence of The read accuracy of the sensor.
Use liquid epoxy resin containing perovskite-type compounds and solid epoxy resin to adjust its content ratio and the type and content of photo-solid compounds to achieve high dielectric constant cured products, while optimizing the resin layer and the second film. peel strength and adhesion.
A resin layer with good image formation after development and thermal curing is achieved, and good adhesion and peelability between the resin layer and the second film are improved, thereby improving the dielectric constant and image stability of the sensor.
Smart Images

Figure BDA0005140758530000211 
Figure BDA0005140758530000231 
Figure BDA0005140758530000261
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated structure, a cured product of a resin layer in the laminated structure, and an electronic component having the cured product. Background Art
[0002] Fingerprint detection devices are used as identity authentication tools in portable terminals and the like. In particular, in the case of devices that require high fingerprint authentication accuracy (such as smartphones), capacitive fingerprint authentication sensors are used. Its working principle is as follows: the difference in charge generated in the sensor due to the concave and convex of the fingerprint is read by an electrode to identify the fingerprint. For example, a semiconductor device that can be used as a capacitive fingerprint detection device is disclosed in Patent Document 1.
[0003] The fingerprint authentication sensor uses an FC-BGA package, in which the top side (surface side) becomes the sensor surface, and components such as an IC chip are mounted on the bottom side (back side) and solder balls are arranged. The sensor surface of the fingerprint authentication sensor requires high reading accuracy, so the insulating protective film formed on the circuit substrate for the sensor surface is required to have flatness and a high dielectric constant.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-71307 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] It is considered that the insulating protective film for the sensor surface is formed by, for example, using a laminated structure including a first film (support), a resin layer, and a second film (protective film) in this order. That is, it is considered that the second film is peeled off from the resin layer of the laminated structure, the resin layer is laminated on the circuit board, and then the resin layer is cured to form the insulating protective film (cured product) for the sensor surface.
[0009] However, good adhesion between the resin layer and the second film is required until the step of peeling the second film from the laminated structure, and good peelability between the resin layer and the second film is required in the step of peeling the second film from the laminated structure. That is, in the laminated structure, the condition of having a resin layer that can obtain a cured product with a high dielectric constant is satisfied, and further, it is particularly important that both the adhesiveness and peelability of the resin layer and the second film are good.
[0010] In addition to these, in order to obtain an insulating protective film with a fine pattern, the resin layer needs to have good image forming properties after development and before heat curing, and further, good image forming properties after heat curing. The reason for this is that, depending on the resin layer of the laminated structure, the image forming properties are good just after development, but the resin contained in the resin layer softens before curing due to heating during heat curing, causing the resin to flow and fill the opening, or the line pattern of the resin layer collapses, and the image forming properties after heat curing sometimes deteriorate. It is necessary to control both so that not only the image forming properties after development and before heat curing become good, but also the image forming properties after heat curing become good.
[0011] The object of the present invention made in view of the above-mentioned problems is to provide: a laminated structure having a cured product that can obtain a high dielectric constant, a resin layer that has good image forming properties both after development and before thermal curing and after thermal curing, and good peeling and adhesion between the resin layer and a second film, a cured product of the resin layer in the laminated structure, and an electronic component having the cured product.
[0012] Solutions for solving problems
[0013] The present inventors conducted intensive research and focused on the components of the resin layer that can obtain a cured product with a high dielectric constant. As a result, they found that the above-mentioned purpose can be achieved by using a specific content of a perovskite compound for obtaining a high dielectric constant and further making a specific content of a liquid epoxy resin as a thermosetting resin relative to a solid epoxy resin, thereby completing the present invention. In general, in order to make the image formation property good, the type of carboxyl-containing resin, carboxyl-free photocurable compound and / or photopolymerization initiator is changed, or their content is adjusted. As a result, the present inventors found that by making a specific content of a perovskite compound and further making a specific content of a liquid epoxy resin relative to a solid epoxy resin, all of the above-mentioned purposes can be unexpectedly achieved at the same time.
[0014] The reason why all the above purposes can be achieved simultaneously may not be clear, but it is considered as follows. That is, in order to obtain a cured product with a high dielectric constant, when the content of the perovskite compound is 55 to 85% by mass relative to the total mass of the resin layer on a solid component basis, it is generally believed that the image formation, the peeling and adhesion of the second film to the resin layer will be reduced, and the result is that by making the content of the liquid epoxy resin relative to 100 parts by mass and 150 to 1000 parts by mass on a solid component basis, the deep curing and surface curing during exposure are suitably obtained, and as a result, good image formation is obtained. In addition, the peel strength of the second film and the resin layer is adjusted to an appropriate range, and the peeling and adhesion of the second film and the resin layer are both good, so that it is believed that the dry film, that is, the form of the laminated structure can be maintained.
[0015] In addition, the dielectric constant of the cured product in this specification refers to the dielectric constant of the cured product obtained by subjecting the resin layer in the laminated structure to an exposure step, a development step, and a thermal curing step.
[0016] That is, the above-mentioned object can be achieved by the laminated structure of the present invention.
[0017] The laminate structure is characterized in that it comprises a first film, a resin layer and a second film in this order.
[0018] The resin layer contains: (A) a carboxyl group-containing resin, (B) a photocurable compound not containing a carboxyl group, (C) a photopolymerization initiator, (D) a perovskite compound, and (E) an epoxy resin.
[0019] The content of the perovskite compound (D) is 55 to 85% by mass based on the solid content relative to the total mass of the resin layer.
[0020] The aforementioned (E) epoxy resin comprises a solid epoxy resin and a liquid epoxy resin,
[0021] The content of the liquid epoxy resin is 150 to 1000 parts by mass based on solid content, relative to 100 parts by mass of the solid epoxy resin.
[0022] According to a preferred embodiment of the laminated structure of the present invention, the content of the (D) perovskite type compound is 70 to 85% by mass based on solid content relative to the total mass of the resin layer.
[0023] According to another preferred embodiment of the multilayer structure of the present invention, the (D) perovskite type compound is a divalent metal salt of titanic acid.
[0024] The present invention also relates to a cured product characterized in that the cured product is obtained by curing the resin layer of the laminated structure.
[0025] Furthermore, the present invention relates to an electronic component characterized by comprising the above-mentioned cured product.
[0026] Effects of the Invention
[0027] According to the present invention, there are provided: a laminated structure having a cured product that can obtain a high dielectric constant, a resin layer that has good image forming properties both after development and before thermal curing and after thermal curing, and good peeling and adhesion properties between the resin layer and a second film, a cured product of the resin layer in the laminated structure, and an electronic component having the cured product. DETAILED DESCRIPTION
[0028] The laminated structure of the present invention can obtain a cured product with a high dielectric constant, a resin layer having good image forming properties after development and before thermal curing and good image forming properties after thermal curing, and a laminated structure having good peeling properties and adhesion properties between the resin layer and the second film by the above-mentioned constitution. It should be noted that the dielectric constant of the cured product is preferably 8 or more, more preferably 10 or more in the 10 GHz frequency band.
[0029] The laminated structure of the present invention may be a laminated structure formed by a first film, a resin layer and a second film, or may be a laminated structure including one or more other resin layers between the first film and the resin layer. The components of the other resin layers may be the same as or different from the components of the resin layer mainly disposed between the first film and the second film. As an example of the laminated structure of the present invention, a dry film may be cited.
[0030] [1st film]
[0031] The first film refers to: when the resin layer in the laminated structure is laminated on a substrate formed with a circuit, it has the function of supporting the resin layer, and is obtained by applying a curable resin composition for forming the resin layer. As the first film, for example, a film formed by a thermoplastic resin such as a polyester film such as polyethylene terephthalate and polyethylene naphthalate, a polyimide film, a polyamide-imide film, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a polystyrene film, etc. can be used. Among these, from the viewpoints of heat resistance, mechanical strength, operability, etc., a polyester film can be suitably used. The thickness of the first film is not particularly limited, and can be appropriately selected according to the purpose in the range of preferably 10 to 150 μm, more preferably 15 to 100 μm, and further more preferably 20 to 75 μm. The surface of the first film provided with a resin layer can be subjected to a demolding treatment. In addition, a conductive resin layer, a metal sputtering layer or an extremely thin copper foil that functions as an antistatic layer can be formed on the surface provided with a resin layer in the first film. As a commercially available product, "E5041" (polyethylene terephthalate film; thickness 25 μm) manufactured by Toyobo Co., Ltd. is exemplified.
[0032] [Resin layer]
[0033] The resin layer contains: (A) a carboxyl-containing resin, (B) a photocurable compound that does not contain a carboxyl group, (C) a photopolymerization initiator, (D) a perovskite compound, and (E) an epoxy resin. The thickness of the resin layer is preferably 5 to 100 μm, more preferably 10 to 90 μm, and even more preferably 20 to 85 μm. By setting it to this range, the requirement for thinning of electronic components can be met. In addition, there are electronic components with various circuit thicknesses depending on the application, but the laminated structure of the present invention can also be fully used for electronic components with large circuit thickness. The resin layer in the laminated structure of the present invention is formed by applying a curable resin composition containing (A) a carboxyl-containing resin, (B) a photocurable compound that does not contain a carboxyl group, (C) a photopolymerization initiator, (D) a perovskite compound, and (E) an epoxy resin on a first film and drying it. Below, the constituent components of the curable resin composition used to form the resin layer are described.
[0034] ((A) Carboxyl-containing resin)
[0035] As the carboxyl-containing resin, various conventionally known resins containing carboxyl groups in the molecule can be used. The carboxyl-containing resin may or may not have an ethylenically unsaturated double bond in the molecule, but from the aspects of light curing and development resistance, a carboxyl-containing photosensitive resin having an ethylenically unsaturated double bond in the molecule is particularly preferred. In the case of having an ethylenically unsaturated double bond in the molecule, the carboxyl-containing resin is equivalent to a photocurable resin. The ethylenically unsaturated double bond is preferably derived from acrylic acid or methacrylic acid or a derivative thereof.
[0036] For the carboxyl-containing resin, the acid value is preferably 20 to 200 mgKOH / g, more preferably 60 to 150 mgKOH / g to cope with the development process. If the acid value is 20 mgKOH / g or more, the solubility in the alkaline aqueous solution increases and the developability becomes good. On the other hand, if the acid value is 200 mgKOH / g or less, the image forming property improves. It should be noted that the acid value in this specification is a value measured by a neutralization titration method using phenolphthalein as an indicator.
[0037] The weight average molecular weight of the carboxyl-containing resin varies depending on the resin skeleton, and is generally in the range of 2,000 to 150,000, preferably in the range of 5,000 to 100,000. By using a carboxyl-containing resin having a weight average molecular weight of 2,000 or more, the dryness to touch of the resin layer can be improved. In addition, by using a carboxyl-containing resin having a weight average molecular weight of 150,000 or less, the developability and storage stability can be improved. It should be noted that the value of the weight average molecular weight (Mw) in this specification is a value measured according to the gel permeation chromatography (GPC) method (polystyrene standard) under the following measuring device and measuring conditions.
[0038] Measuring device: Waters 2695
[0039] Detector: Waters 2414, RI (differential refractometer)
[0040] Column: "HSPgel Column, HR MB-L, 3 μm, 6 mm × 150 mm" made by Waters × 2 + "HSPgel Column, HR1, 3 μm, 6 mm × 150 mm" made by Waters × 2
[0041] Determination conditions:
[0042] Column temperature: 40°C
[0043] RI detector set temperature: 35°C
[0044] Developing solvent: tetrahydrofuran
[0045] Flow rate: 0.5ml / min
[0046] Sample volume: 10 μl
[0047] Sample concentration: 0.5wt%
[0048] The content of the carboxyl group-containing resin is preferably 5 to 30% by mass based on the solid content relative to the total mass of the resin layer.
[0049] As a specific example of carboxyl-containing resin, for example, the following resins (oligomers and polymers, both are acceptable) can be cited. The following carboxyl-containing resins can be used alone or in combination of two or more. It should be noted that in this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate and a mixture thereof, and the same is true for other similar expressions.
[0050] (1) Carboxyl group-containing resins obtained by copolymerization of an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, a lower alkyl (meth)acrylate, or isobutylene.
[0051] (2) Carboxyl group-containing polyurethane resins obtained by the addition polymerization reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing diol compounds such as dimethylol propionic acid and dimethylol butyric acid and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A-based alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0052] (3) A polyurethane resin containing terminal carboxyl groups obtained by reacting the ends of a polyurethane resin with an acid anhydride to obtain a polyurethane resin through a polyaddition reaction of a diisocyanate compound such as an aliphatic diisocyanate, a branched aliphatic diisocyanate, an alicyclic diisocyanate, an aromatic diisocyanate, and a diol compound such as a polycarbonate polyol, a polyether polyol, a polyester polyol, a polyolefin polyol, an acrylic polyol, a bisphenol A-based alkylene oxide adduct diol, and a compound having a phenolic hydroxyl group and an alcoholic hydroxyl group.
[0053] (4) A carboxyl-containing polyurethane resin obtained by the polyaddition reaction of a diisocyanate with a (meth)acrylate of a bifunctional epoxy resin such as a bisphenol A epoxy resin, a hydrogenated bisphenol A epoxy resin, a bisphenol F epoxy resin, a bisphenol S epoxy resin, a dimethylphenol epoxy resin, a biphenol epoxy resin or a partially anhydride-modified product thereof, a carboxyl-containing diol compound and a diol compound.
[0054] (5) A carboxyl group-containing polyurethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule such as hydroxyalkyl (meth)acrylate to the synthesis of the carboxyl group-containing polyurethane resin described in (2) or (4) above to thereby subject the resin to terminal (meth)acrylation.
[0055] (6) A carboxyl group-containing polyurethane resin obtained by adding an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate to the synthesis of the carboxyl group-containing polyurethane resin described in (2) or (4) above, and subjecting the resin to terminal (meth)acryloylation.
[0056] (7) A carboxyl group-containing resin obtained by reacting a polyfunctional epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chains.
[0057] (8) A carboxyl group-containing resin obtained by reacting a polyfunctional epoxy resin obtained by epoxidizing the hydroxyl groups of a bifunctional epoxy resin with epichlorohydrin with (meth)acrylic acid and adding a dibasic acid anhydride to the generated hydroxyl groups.
[0058] (9) A carboxyl group-containing polyester resin obtained by reacting a polyfunctional oxetane resin with a dicarboxylic acid and adding a dibasic acid anhydride to the generated primary hydroxyl group.
[0059] (10) A carboxyl-containing resin obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide to obtain a reaction product, reacting the reaction product with an unsaturated group-containing monocarboxylic acid, and reacting the reaction product obtained with a polyacid anhydride.
[0060] (11) A carboxyl-containing resin obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate to obtain a reaction product, reacting the reaction product with a monocarboxylic acid containing an unsaturated group, and reacting the reaction product obtained with a polyacid anhydride.
[0061] (12) A carboxyl-containing resin obtained by reacting an epoxy compound having multiple epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule such as p-hydroxyphenylethanol with a monocarboxylic acid containing an unsaturated group such as (meth)acrylic acid, so that the alcoholic hydroxyl group of the obtained reaction product reacts with a polyacid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, adipic anhydride, etc.
[0062] (13) A carboxyl group-containing resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule such as glycidyl (meth)acrylate or α-methylglycidyl (meth)acrylate to the carboxyl group-containing resin described in (1) to (12) above.
[0063] ((B) Photocurable compound not containing a carboxyl group)
[0064] The photocurable compound not containing a carboxyl group refers to a compound containing an ethylenically unsaturated double bond but not containing a carboxyl group, and may include a photocurable polymer, a photocurable oligomer, a photocurable monomer, etc., and may be a mixture thereof. By including a photocurable compound not containing a carboxyl group, the strength of the cured product can be improved. The photocurable compound not containing a carboxyl group can be used alone or in combination of two or more.
[0065] Examples of the photocurable polymer and the photocurable oligomer include unsaturated polyester oligomers, (meth)acrylate oligomers, etc. Examples of the (meth)acrylate oligomer include epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol epoxy (meth)acrylate, urethane (meth)acrylate, epoxyurethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and polybutadiene-modified (meth)acrylate.
[0066] Examples of the photocurable monomer include: alkyl (meth)acrylates such as 2-ethylhexyl (meth)acrylate and cyclohexyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; mono- or di-(meth)acrylates of alkylene oxide derivatives such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; hexanediol, trimethylolpropane, pentaerythritol, di(trimethylol)propane, and dipentaerythritol. , polyols such as trihydroxyethyl isocyanurate or their ethylene oxide or propylene oxide adducts (meth)acrylates; (meth)acrylates of ethylene oxide or propylene oxide adducts of phenols such as phenoxyethyl (meth)acrylate and polyethoxy di(meth)acrylate of bisphenol A; (meth)acrylates of glycidyl ethers such as glycerol diglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and melamine (meth)acrylate.
[0067] In addition, as a photocurable compound not containing a carboxyl group, a photocurable compound obtained as follows is also preferred: a phenol compound having two or more phenolic hydroxyl groups in a molecule is obtained by a condensation reaction of a polyhydroxymethyl form of bisphenol A or bisphenol F with phenols, a part of or all of the phenolic hydroxyl groups of the phenol compound having two or more phenolic hydroxyl groups in the molecule is converted into an oxyalkyl group having an alcoholic hydroxyl group, and (meth) acrylic acid is added to the terminal hydroxyl group of the generated oxyalkyl group, thereby obtaining a photocurable compound.
[0068] As a commercially available product, DA-600 manufactured by Sanyo Chemical Industries, Ltd. can be cited, for example.
[0069] The content of the photocurable compound not containing a carboxyl group is preferably 0.1 to 30% by mass, more preferably 1 to 10% by mass, based on the solid content relative to the total mass of the resin layer.
[0070] ((C) Photopolymerization initiator)
[0071] The photopolymerization initiator is used to react the carboxyl-containing resin and / or the photocurable compound not containing a carboxyl group by exposure. As the photopolymerization initiator, any known substance can be used. The photopolymerization initiator can be used alone or in combination of two or more.
[0072] Examples of the photopolymerization initiator include bisacylphosphine oxides such as bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and bisacylphosphine oxides such as bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide. 2,6-dichlorobenzoyldiphenylphosphine oxide, methyl 2,4,6-trimethylbenzoylphenylphosphine oxide, 2-methylbenzoyldiphenylphosphine oxide, isopropyl pivaloylphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and other monoacylphosphine oxides; ethyl phenyl (2,4,6-trimethylbenzoyl)phosphine oxide, 1-hydroxy-cyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one and other hydroxyacetophenones Benzoin, benzil, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, benzoin n-butyl ether and other benzoins; benzoin alkyl ethers; benzophenone, p-methyl benzophenone, Michler's ketone, methyl benzophenone, 4,4'-dichlorobenzophenone, 4,4'-bis(diethylamino)benzophenone and other benzophenones; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino) -2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone and other acetophenones; thioxanthones such as thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-diisopropylthioxanthone; anthraquinones such as anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, 2-aminoanthraquinone; ketals such as acetophenone dimethyl ketal and benzil dimethyl ketal; benzoic acid esters such as ethyl-4-dimethylamino benzoate, 2-(dimethylamino)ethyl benzoate, and ethyl p-dimethylbenzoate;Oxime esters such as 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-ethanone 1-(O-acetyl oxime); titanocenes such as bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-pyrrol-1-yl)ethyl)phenyl]titanium; 2-nitrofluorene phenyl disulfide, butyroquinone, anisole ether, azobisisobutyronitrile, tetramethylthiuram disulfide, etc. ;
[0073] As commercial products of acetophenone-based photopolymerization initiators, Omnirad 907, 369, 369E, 379, etc. manufactured by IGM Resins can be cited. In addition, as commercial products of acylphosphine oxide-based photopolymerization initiators, Omnirad TPO, 819, etc. manufactured by IGM Resins can be cited. As commercial products of oxime ester-based photopolymerization initiators, Irgacure OXE01, OXE02, OXE03, OEX04 manufactured by BASF Japan Co., Ltd., N-1919, ADEKA ARKLS NCI-831, NCI-831E manufactured by ADEKA Co., Ltd., TR-PBG-304, 345, 411, 458 manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd. can be cited. As commercial products of titanocene-based photopolymerization initiators, Omnirad 784 manufactured by IGM Resins can be cited. Examples of commercially available products of thioxanthone-based photopolymerization initiators include KAYACUREDETX-S manufactured by Nippon Kayaku Co., Ltd.
[0074] In addition, carbazole oxime ester compounds described in JP-A-2004-359639, JP-A-2005-097141, JP-A-2005-220097, JP-A-2006-160634, JP-A-2008-094770, JP-T-2008-509967, JP-T-2009-040762, and JP-A-2011-80036 can be cited.
[0075] As the photopolymerization initiator, from the viewpoint of improving the deep curing property, a compound that absorbs h-ray (405 nm) and / or g-ray (436 nm) is more preferred. Specifically, Omnirad TPO and 819 manufactured by IGM Resins, Irgacure OEX04 manufactured by BASF Japan Co., Ltd., NCI-831E manufactured by ADEKA Co., Ltd., TR-PBG-411 and 458 manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd., and Omnirad 784 manufactured by IGM Resins can be cited.
[0076] The content of the photopolymerization initiator is preferably 0.1 to 3% by mass based on the solid content relative to the total mass of the resin layer.
[0077] In combination with the above-mentioned photopolymerization initiator, a photoinitiator aid or sensitizer may also be used. As the photoinitiator aid or sensitizer, tertiary amine compounds and xanthone compounds may be mentioned. In addition, the photoinitiator aid or sensitizer may be used alone or in combination of two or more.
[0078] ((D) Perovskite-type compounds)
[0079] As the perovskite compound, a divalent metal salt of titanic acid is preferred. As the divalent metal salt of titanic acid, for example, barium titanate, calcium titanate, strontium titanate, bismuth titanate, magnesium titanate, barium neodymium titanate, barium tin titanate, lead titanate, and a composite oxide containing any of them can be cited. As the divalent metal salt of titanic acid, it is particularly preferred to use at least one of barium titanate and calcium titanate in terms of high dielectric constant and chemical stability of the composition. Furthermore, from the viewpoint of improving the peelability of the second film, the perovskite compound is preferably barium titanate.
[0080] In order to obtain sufficient wettability with organic compounds such as carboxyl group-containing resins and epoxy resins, such perovskite type compounds may be surface-treated with a coupling agent such as aminosilane, mercaptosilane or vinylsilane.
[0081] This perovskite compound preferably has an average particle size of 0.01 to 10.0 μm. By using a perovskite compound with an average particle size within this range, the image formation can be further improved. It should be noted that the average particle size refers to the value of D50 when the particle size distribution is made on a volume basis, which can be obtained using a laser diffraction particle size distribution measuring device or a measuring device based on a dynamic light scattering method. As a measuring device based on the laser diffraction method, Microtrac MT3300EXII made by MicrotracBELCorp. can be cited, and as a measuring device based on the dynamic light scattering method, Nanotrac Wave II UT151 made by MicrotracBEL Corp. can be cited. The measurement sample can preferably be made by dispersing the perovskite compound in PMA (propylene glycol monomethyl ether acetate).
[0082] In the present invention, the content of the perovskite compound is 55 to 85% by mass based on the solid content relative to the total mass of the resin layer, and is preferably 70 to 85% by mass from the viewpoint of obtaining a higher dielectric constant. In addition, from the viewpoint of the peelability and image formation of the second film, the content of the perovskite compound is preferably 70 to 83% by mass.
[0083] ((E) Epoxy resin)
[0084] Epoxy resins include solid epoxy resins and liquid epoxy resins. In this specification, solid epoxy resin refers to an epoxy resin that is solid at 20°C. The concept of solid epoxy resin includes the concepts of semi-solid epoxy resin and crystalline epoxy resin. The various compounds contained in the concept of solid epoxy resin can be used alone or in combination of two or more. It should be noted that semi-solid epoxy resin refers to an epoxy resin that is solid at 20°C and liquid at 40°C. Crystalline epoxy resin refers to an epoxy resin with strong crystallinity, which means: at 20°C, the polymer chains are regularly and neatly arranged, and it is a solid epoxy resin, but when melted, it becomes a low-viscosity epoxy resin equivalent to a liquid resin.
[0085] In this specification, liquid epoxy resin refers to an epoxy resin that is liquid at 20°C. The determination of liquid state is based on the 2nd appendix "Method for Confirming Liquid State" of the Provincial Order Concerning Tests and Properties of Dangerous Substances (Autonomy Provincial Order No. 1 of 1918). Specifically, it is carried out by the method described in paragraphs 23 to 25 of Japanese Patent Application Laid-Open No. 2016-079384. In this way, liquid epoxy resin can be distinguished from solid epoxy resin for determination. Liquid epoxy resin must be determined as liquid in the "Method for Confirming Liquid State", and its viscosity is preferably 100 to 30,000 mPa·s at 25°C.
[0086] Examples of the solid epoxy resin include naphthalene-type epoxy resins such as EPICLON HP-4700 (naphthalene-type epoxy resin) manufactured by DIC Corporation and NC-7000 (naphthalene skeleton-containing multifunctional epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; epoxides of condensates of phenols and aromatic aldehydes having a phenolic hydroxyl group such as EPPN-502H (trisphenol epoxy resin) manufactured by Nippon Kayaku Co., Ltd. (trisphenol-type epoxy resin); EPICLON HP-4700 (naphthalene-type epoxy resin) manufactured by DIC Corporation and NC-7000 (naphthalene skeleton-containing multifunctional epoxy resin) manufactured by Nippon Kayaku Co., Ltd. HP-7200H, HP-7200L (dicyclopentadiene skeleton-containing multifunctional epoxy resins) and other dicyclopentadiene aralkyl type epoxy resins; NC-3000H (biphenyl skeleton-containing multifunctional epoxy resins) manufactured by Nippon Kayaku Co., Ltd. and other biphenyl aralkyl type epoxy resins; NC-3000L and other biphenyl / phenol novolac type epoxy resins manufactured by Nippon Kayaku Co., Ltd.; EPICLON N660, N690, N770 manufactured by DIC Corporation, EOCN-104S manufactured by Nippon Kayaku Co., Ltd. and other novolac type epoxy resins; triglycidyl isocyanurate such as TEPIC manufactured by Nissan Chemical Co., Ltd., etc.
[0087] Examples of the semi-solid epoxy resin include bisphenol A type epoxy resins such as EPICLON 860, EXA-4816, and EPICLON EXA-4822 manufactured by DIC Corporation, EPOTOHTO YD-134 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., jER834 and jER872 manufactured by Mitsubishi Chemical Corporation, and ELA-134 manufactured by Sumitomo Chemical Co., Ltd.; and phenol novolac type epoxy resins such as EPICLON N-740 manufactured by DIC Corporation.
[0088] In addition, as the crystalline epoxy resin, for example, those having a biphenyl structure, a sulfide structure, a phenylene structure, a naphthalene structure, etc. can be used. Biphenyl type epoxy resins are provided, for example, as JER YX4000, YX4000H, YL6121H, YL6640, and YL6677 manufactured by Mitsubishi Chemical Corporation, diphenyl sulfide type epoxy resins are provided, for example, as EPOTOHTO YSLV-120TE manufactured by NIPPON STEEL Chemical & Material Co., Ltd., phenylene type epoxy resins are provided, for example, as EPOTOHTO YDC-1312 manufactured by NIPPONSTEEL Chemical & Material Co., Ltd., and naphthalene type epoxy resins are provided, for example, as EPICLON HP-4032 and HP-4032D manufactured by DIC Corporation. Moreover, as a crystalline epoxy resin, EPOTOHTO YSLV-90C manufactured by NIPPON STEEL Chemical & Material Co., Ltd. and TEPIC-S (triglycidyl isocyanurate) manufactured by Nissan Chemical Co., Ltd. can also be used.
[0089] As liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, glycidylamine type epoxy resin, aminophenol type epoxy resin, alicyclic epoxy resin etc. can be cited. By including liquid epoxy resin, the flexibility of the laminated structure is excellent. Liquid epoxy resin can be used alone or in combination of two or more. Liquid epoxy resin is preferably at least any one of bisphenol A type epoxy resin, bisphenol F type epoxy resin and bisphenol E type epoxy resin.
[0090] Examples of the liquid epoxy resin include jER828 (liquid bisphenol A epoxy resin) manufactured by Mitsubishi Chemical Corporation, EPICLON 850-S (liquid bisphenol A epoxy resin) manufactured by DIC Corporation, EPOX MK R710 (liquid bisphenol E epoxy resin) manufactured by Printec Co., Ltd., and ZX1059 (a mixture of liquid bisphenol A epoxy resin and liquid bisphenol F epoxy resin) manufactured by NIPPON STEEL Chemical & Material Co., Ltd.
[0091] The content of the epoxy resin is, for example, 0.1 to 30% by mass based on the solid content relative to the total mass of the resin layer.
[0092] From the viewpoint of the adhesion and image formation of the second film and the resin layer, the content of the liquid epoxy resin is 150 to 1000 parts by mass relative to 100 parts by mass of the solid epoxy resin, based on the solid content. In addition, from the viewpoint of making the adhesion of the second film and the resin layer better, the content of the liquid epoxy resin is preferably 180 parts by mass or more relative to 100 parts by mass of the solid epoxy resin, based on the solid content. On the other hand, from the viewpoint of making the peelability of the second film and the resin layer better, the content of the liquid epoxy resin is preferably 750 parts by mass or less relative to 100 parts by mass of the solid epoxy resin, based on the solid content. From the viewpoint of making the adhesion and peelability of the second film and the resin layer better, and further setting the peel strength to a suitable range, the content of the liquid epoxy resin is preferably 180 to 750 parts by mass relative to 100 parts by mass of the solid epoxy resin, based on the solid content.
[0093] (Organic Solvent)
[0094] The curable resin composition for obtaining the resin layer of the laminated structure of the present invention may contain an organic solvent for the purpose of preparing the curable resin composition or adjusting the viscosity when applied to the first film. As the organic solvent, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, diethylene glycol monoethyl ether acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, petroleum naphtha, and solvent naphtha, and the like are well-known and commonly used organic solvents. As a product of an organic solvent, Jukisol CA (carbitol acetate, diethylene glycol monoethyl ether acetate) manufactured by DOW CHEMICAL JAPAN LIMITED is mentioned, for example.
[0095] The content of the organic solvent is not particularly limited and can be appropriately set according to the target viscosity so that the curable resin composition can be easily prepared.
[0096] (Other added ingredients)
[0097] The resin layer of the laminated structure of the present invention may be further mixed with substances known in the field of electronic materials, such as thermosetting resins other than epoxy resins, polymerization inhibitors, cyanate compounds, elastomers, mercapto compounds, thixotropic agents, adhesion promoters, block copolymers, chain transfer agents, copper damage inhibitors, antioxidants, rust inhibitors, fine powder silica, organic bentonite, thickeners (such as montmorillonite), silicone-based, fluorine-based, polymer-based defoamers, dispersants, colorants and leveling agents as needed. As commercially available dispersants, for example, DisperBYK-111 manufactured by BYK Corporation can be cited.
[0098] [Second film]
[0099] The second film is provided on the surface of the resin layer opposite to the first film for the purpose of preventing dust and the like from adhering to the surface of the resin layer of the laminated structure and improving operability. As the second film, for example, the first film can be used. Among these, polyester film, polyethylene film, polypropylene film, and films obtained by subjecting the surfaces of these films to demolding treatment are preferred. The thickness of the second film is not particularly limited and can be appropriately selected according to the application in the range of preferably 10 to 150 μm, more preferably 12.5 to 100 μm, and further more preferably 15 to 50 μm. The surface of the second film provided with the resin layer can be subjected to demolding treatment.
[0100] The second film preferably has an arithmetic mean surface roughness Ra of 0.10 μm or more on the surface in contact with the resin layer. When Ra is 0.10 μm or more, the adhesion between the resin layer and the second film can be further improved. On the other hand, from the viewpoint of improving both the peelability and adhesion between the resin layer and the second film, Ra of the second film is preferably 1.0 μm or less, and more preferably 0.80 μm or less.
[0101] The specific measurement method of the arithmetic mean surface roughness Ra is described below. The arithmetic mean surface roughness Ra is a value measured using a shape measurement laser microscope (e.g., VK-X100 manufactured by KEYENCE CORPORATION). After starting the main body (control unit) of the shape measurement laser microscope (same VK-X100) and the VK observation application (VK-H1VX manufactured by KEYENCE CORPORATION), place the sample to be measured (the second film) on the xy stage. Turn the lens converter of the microscope unit (VK-X110 manufactured by KEYENCE CORPORATION), select the objective lens with a magnification of 10 times, and roughly adjust the focus and brightness in the image observation mode of the VK observation application (same VK-H1VX). Operate the xy stage and adjust it in such a way that the part of the sample surface to be measured becomes the center of the screen. Replace the objective lens with a magnification of 10 times with a magnification of 50 times, and focus on the surface of the sample under the automatic focus function of the image observation mode of the VK observation application (same VK-H1VX). Select the simple mode of the shape measurement tablet of the VK observation application (same VK-H1VX), press the measurement start button, measure the surface shape of the sample, and obtain the surface image file. Start the VK analysis application (VK-H1XA made by KEYENCE CORPORATION), display the obtained surface image file, and then perform slope correction. It should be noted that the lateral observation measurement range in the measurement of the surface shape of the sample is set to 270μm. Display the line roughness window, select JISB0601-1994 in the parameter setting area, select the horizontal line from the measurement line button, display the horizontal line at any position in the surface image, and press the OK button to obtain the numerical value of the arithmetic mean surface roughness Ra. Furthermore, display the horizontal lines at 4 different locations in the surface image to obtain the numerical values of each arithmetic mean surface roughness Ra. Calculate the average value of the 5 values obtained respectively as the arithmetic mean surface roughness Ra of the sample surface.
[0102] As the second film having the above-mentioned arithmetic mean surface roughness Ra, when a thermoplastic resin film is used, fillers are added to the resin when the film is formed into a film, or the film surface is sandblasted, or the surface can be formed into a specified shape by hairline processing, matte coating, or chemical etching, etc., so that a thermoplastic resin film having the above-mentioned arithmetic mean surface roughness Ra can be obtained. For example, when a filler is added to the resin, the arithmetic mean surface roughness Ra can be controlled by adjusting the particle size and / or addition amount of the filler. In addition, when sandblasting is performed, the arithmetic mean surface roughness Ra can be controlled by adjusting the processing conditions such as the sandblasting material and / or the sandblasting pressure.
[0103] Commercially available products of the second film having an arithmetic mean surface roughness Ra of 0.1 μm or more include, for example: Alphan "MA-411", "MA-420", "MA-430", "E-201F", "ER-440" (biaxially stretched polypropylene films) manufactured by OjiF-Tex Co., Ltd., "Lumirror X42", "Lumirror X43", "Lumirror X44" manufactured by Toray Industries, Ltd., Emblet "PTH-12", "PTH-25", "PTHA-25", "PTH-38" manufactured by UNITIKA LTD., etc.
[0104] [Method for forming a laminated structure]
[0105] When forming a laminated structure, first, a curable resin composition for forming a resin layer is prepared. That is, each component such as (A) a carboxyl-containing resin is mixed separately, pre-mixed in a mixer, and then kneaded in a three-roll mill to prepare a curable resin composition. The prepared curable resin composition is applied to the first film with a uniform thickness using a comma coater, a blade coater, etc. Thereafter, the applied curable resin composition is usually dried at a temperature of 40 to 130° C. for 1 to 30 minutes to form a resin layer. Furthermore, a second film is bonded to the surface of the resin layer on the opposite side of the first film to form a laminated structure. In addition, when the laminated structure is in the form of an elongated strip, it can be rolled up to form a rolled laminated structure. The rolled laminated structure can be cut into a specified width as needed.
[0106] [Method for forming a circuit board using a cured resin layer]
[0107] The formation of the cured product of the resin layer on the circuit substrate can be carried out by a method including the following steps:
[0108] The second film in the laminated structure is peeled off, the resin layer is attached to the substrate on which the circuit is formed, and the first film and the resin layer are laminated on the substrate;
[0109] an exposure step of irradiating a predetermined portion of the resin layer with active energy rays;
[0110] A developing step of removing the area of the resin layer not irradiated with the active energy ray after the exposure step; and
[0111] A step of forming a cured product by heating the resin layer after the development step.
[0112] In addition, the step of peeling the first film from the resin layer may be performed before or after the exposure step.
[0113] (Step of attaching a resin layer to a substrate having a circuit formed thereon)
[0114] As a process for attaching the resin layer to the circuit substrate, it is preferred to use a vacuum laminator or the like, peel off the second film from the resin layer, and laminate the resin layer on the substrate formed with the circuit under pressure and heating. By using such a vacuum laminator, the resin layer of the laminated structure is closely attached to the surface of the circuit substrate, so that there is no mixing of bubbles, and the filling property of the concave part of the circuit substrate surface is also improved. The pressurization condition is preferably about 0.1 to 2.0 MPa, and the heating condition is preferably 40 to 120°C.
[0115] (Exposure process)
[0116] In the exposure step, for example, the exposure dose is 50 to 1000 mJ / cm 2 The resin layer is irradiated with active energy rays under the conditions of, thereby, the resin layer can be photocured into a predetermined pattern shape. The irradiation of active energy rays is performed by irradiation with ultraviolet rays, electron beams, chemical rays, etc. As a method of irradiating a predetermined portion with active energy rays, a method of selectively irradiating active energy rays through a photomask formed with a predetermined pattern may be used, or a direct drawing device (for example, a laser direct imaging device that directly draws an image with a laser using CAD data from a computer) may be used.
[0117] As an exposure machine used for irradiation with active energy rays, it is preferred to use a device equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, a UV-LED, etc., and to irradiate ultraviolet rays in the range of 350 to 450 nm. As a lamp light source or a laser light source of a direct-drawing machine, it is preferred to use a device having a maximum wavelength in the range of 350 to 410 nm.
[0118] (Development Process)
[0119] In the development step, after the first film is peeled off, the unexposed portion is removed by development based on an alkaline aqueous solution, and a negative pattern-shaped solidified product can be formed. As a developing method, a well-known method such as immersion can be used. In addition, as a developer, sodium carbonate, potassium carbonate, potassium hydroxide, amines, imidazoles such as 2-methylimidazole, alkaline aqueous solutions such as tetramethylammonium hydroxide aqueous solution (TMAH), or a mixture thereof can be used.
[0120] (Solidified Product Forming Step)
[0121] In the step of forming a cured product, after the developing step, the cured product is completely thermally cured, thereby obtaining a cured product with a high dielectric constant. The heating conditions are, for example, 120° C. to 180° C. for 5 minutes to 120 minutes. It should be noted that in the step of forming a cured product, not only thermal curing based on heating but also photocuring based on ultraviolet irradiation can be used.
[0122] As a substrate formed with a circuit, for example, in addition to a printed circuit board and a flexible printed circuit board formed with a circuit in advance by copper, etc., there can also be cited: using paper phenol resin, paper epoxy resin, glass cloth epoxy resin, glass polyimide, glass cloth / non-woven epoxy resin, glass cloth / paper epoxy resin, synthetic fiber epoxy resin, using materials such as fluororesin / polyethylene / polyphenylene ether (polyphenylene oxide) / cyanate, etc., copper-clad laminates of all grades (FR-4, etc.), metal substrates, polyimide films, PET films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, and those formed with a circuit on a wafer, etc. It is not limited to these, and well-known and commonly used circuit substrates can be used.
[0123] [Cured resin layer]
[0124] The cured product is obtained by curing the resin layer. For example, it is obtained by implementing the above-mentioned process. Specifically, the cured product of the present invention is obtained as follows: the second film in the stacked structure is peeled off, the resin layer and the first film are exposed, and then the first film is peeled off, and the resin layer is only in a state, and then developed and heat-cured in sequence, thereby obtaining. The obtained cured product is useful as a cured product with a high dielectric constant, and is also suitable as a cover layer or solder mask (insulating cured product) formed on a flexible printed circuit board.
[0125] [Electronic component characterized by having a cured product of a resin layer]
[0126] The present invention also provides an electronic component having a cured product of a resin layer. The electronic component in the present invention refers to a component used in an electronic circuit, and is preferably a fingerprint authentication sensor. In addition, it can also be an active component such as a transistor, a light-emitting diode, a laser diode, or a passive component such as a capacitor, an inductor, and a connector.
[0127] Example
[0128] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples. It should be noted that all "parts" and "%" below are based on mass unless otherwise specified.
[0129] ((A) Synthesis Example 1 of Carboxyl Group-Containing Resin)
[0130] In a flask equipped with a thermometer, a stirrer, a dropping funnel and a reflux condenser, 325.0 parts by mass of dipropylene glycol monomethyl ether as a solvent was heated to 110° C., and a mixture of 174.0 parts by mass of methacrylic acid, 174.0 parts by mass of ε-caprolactone-modified methacrylic acid (average molecular weight 314), 77.0 parts by mass of methyl methacrylate, 222.0 parts by mass of dipropylene glycol monomethyl ether, and 12.0 parts by mass of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, PERBUTYLO) as a polymerization catalyst was added dropwise over 3 hours, and the mixture was further stirred at 110° C. for 3 hours to deactivate the polymerization catalyst, thereby obtaining a resin solution. After the resin solution is cooled, 289.0 parts by mass of Cyclomer M100 manufactured by Daicel Corporation, 3.0 parts by mass of triphenylphosphine and 1.3 parts by mass of hydroquinone monomethyl ether are added, the temperature is raised to 100°C, and the mixture is stirred, thereby performing a ring-opening addition reaction of the epoxy group to obtain a carboxyl-containing resin. The carboxyl-containing resin thus obtained is as follows: the solid content is 45.5% by mass, and the acid value of the solid content is 79.8 mgKOH / g. It should be noted that the carboxyl-containing resin is equivalent to the carboxyl-containing resin of (13) in the above ((A) carboxyl-containing resin). It should be noted that, as mentioned above, polystyrene was used as a standard substance and measured according to gel permeation chromatography (GPC), and the result was 20,000.
[0131] (Examples 1 to 15 and Comparative Examples 1 to 4)
[0132] After preparing the curable resin composition according to the following method, a laminated structure was produced.
[0133] (Preparation of curable resin composition)
[0134] According to the formulations described in Tables 1 and 2, the components described in the Examples and Comparative Examples were mixed, premixed in a stirrer, and then kneaded in a three-roll mill to prepare a curable resin composition for preparing a laminated structure. It should be noted that all values other than the organic solvent in the table are values of the solid content.
[0135] (Fabrication of Laminated Structure)
[0136] A polyethylene terephthalate film ("E5041" manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm was prepared as the first film. The curable resin composition obtained above was applied to the film and dried at a temperature of 80°C for 15 minutes to form a resin layer with a thickness of 25 μm after drying. Next, MA-411 (a biaxially stretched polypropylene film manufactured by Oji F-Tex Co., Ltd.; Ra = 0.45 μm) was laminated as the second film to obtain the laminated structures of Examples 1 to 14 and Comparative Examples 1 to 4.
[0137] In Example 15, a laminated structure was obtained in the same manner as in Example 5 except that the second film was changed to MA-430 (a biaxially stretched polypropylene film manufactured by Oji F-Tex Co., Ltd.; Ra=0.75 μm).
[0138] Table 1: Examples
[0139] [Table 1]
[0140]
[0141] The “content of the perovskite compound” in Table 1 above indicates the mass % of the perovskite compound when the “total solid content of the curable resin composition” is taken as 100 mass %.
[0142] *1: DA-600: Dipentaerythritol hexaacrylate manufactured by Sanyo Chemical Industries, Ltd.
[0143] *2: Omnirad 819: Acylphosphine oxide-based photopolymerization initiator manufactured by IGM Resins BV
[0144] *3: Disperbyk-111: Dispersant manufactured by BYK Corporation
[0145] *4: Barium titanate: Perovskite compound manufactured by Sakai Chemical Industry Co., Ltd. (average particle size = 0.5 μm)
[0146] *5: Calcium titanate: a perovskite compound manufactured by Denka Company Limited (average particle size = 5 μm).
[0147] *6: EPICLON HP-7200L: Solid epoxy resin manufactured by DIC Corporation, multifunctional epoxy resin containing a dicyclopentadiene skeleton
[0148] *7: NC-3000H: Solid epoxy resin, biphenyl aralkyl type epoxy resin manufactured by Nippon Kayaku Co., Ltd.
[0149] *8: jER828: Liquid epoxy resin manufactured by Mitsubishi Chemical Corporation (viscosity at 25°C = 13000 mPa·s), bisphenol A type epoxy resin
[0150] *9: EPICLON 850-S: liquid epoxy resin manufactured by DIC Corporation (viscosity at 25°C = 14000 mPa·s), bisphenol A type epoxy resin
[0151] *10: EPOX MK R710: Liquid epoxy resin manufactured by Printec Co., Ltd. (viscosity at 25°C = 2700 mPa·s), bisphenol E type epoxy resin
[0152] *11: ZX1059: Liquid epoxy resin (viscosity at 25°C = 2,500 mPa·s) manufactured by NIPPON STEEL Chemical & Material Co., Ltd., a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin
[0153] *12: Jukisol CA: Organic solvent manufactured by DOW CHEMICAL JAPAN LIMITED
[0154] Table 2: Comparative Examples
[0155] [Table 2]
[0156]
[0157] The information concerning the compounds *1 to *12 in Table 2 is the same as the information concerning the compounds *1 to *12 in Table 1.
[0158] (Adhesion of the Second Film)
[0159] In the preparation of the above-mentioned laminated structure, the adhesion between the resin layer and the second film when the second film was bonded to the surface of the resin layer was evaluated using a roll laminator (VA-770 manufactured by Taisei Laminator Co., Ltd.) with the lamination roll temperature set at 50°C and the press pressure set at 0.2 MPa.
[0160] ⊚: In the prepared laminated structure, the resin layer and the second film are well adhered to each other over the entire surface.
[0161] ○: In the prepared laminated structure, only slight lifting of the second film was observed at the end portion, but the level was not problematic for use as a laminated structure.
[0162] ×: In the prepared laminated structure, the second film was not attached to the resin layer over the entire surface.
[0163] (Removability of the second film)
[0164] The laminated structures prepared in Examples 1 to 15 and Comparative Examples 1 to 4 were cut into a width of 10 cm and a length of 30 cm. After the laminated structures were left at room temperature (20° C.) for 10 minutes, the second film of the laminated structures was peeled off from the resin layer at 90 degrees upward relative to the surface of the resin layer, and the presence or absence of damage to the resin layer was observed. If the resin layer can be peeled off without being damaged, it can be said that the peelability between the resin layer and the second film is good.
[0165] ⊚: No adhesion of the resin layer to the second film was observed, and no destruction of the resin layer was confirmed.
[0166] ○: Adhesion of the resin layer to the second film was slightly observed, but there was no problem in using the laminated structure.
[0167] ×: Adhesion of the resin layer to the second film was much observed, and significant destruction of the entire resin layer was confirmed, which caused problems in use as a laminated structure.
[0168] (Image formation)
[0169] A double-sided copper-clad laminate (copper foil thickness 35 μm, substrate thickness 1.6 mm, substrate size 150 mm×95 mm, manufactured by Showa Denko Materials Co., Ltd.) was etched at a rate of 1 μm / m using MECetchBOND CZ8101 manufactured by MEC Co., Ltd. 2 CZ treatment (roughening treatment) was performed to obtain a roughening substrate. After peeling off the second film from the stacked structure, CVP-300 manufactured by Nikko-Materials Co., Ltd. was used to laminate the resin layer and the first film on the roughening substrate in such a manner that the resin layer contacts the roughening surface of the roughening substrate. It should be noted that the lamination was performed as follows: in a chamber at 70° C., under a vacuum pressure of 3 hPa, a vacuum time of 20 seconds, a pressurization time of 90 seconds, and a pressurization pressure of 0.4 MPa.
[0170] The resin layer laminated on the roughened substrate was exposed to light using an EXP-2960 (light source: short arc lamp, parallel light exposure machine) manufactured by ORC MANUFACTURING CO., LTD. (ORC) at a cumulative exposure dose of 200 mJ / cm 2 After pattern exposure, the first film was peeled off and then developed using a 1 wt % sodium carbonate aqueous solution at 30° C. and a spray pressure of 0.2 MPa for 60 seconds to obtain a cured product pattern after development.
[0171] The opening diameter of the cured product pattern obtained above was observed, and the image forming properties after development and before thermal curing were evaluated.
[0172] ○: Open your mouth well.
[0173] △: Open, but the opening shape is skewed.
[0174] ×: Unable to speak.
[0175] Then, the cured product pattern after the development was irradiated with 1000 mJ / cm in a UV conveyor oven. 2 After exposure to ultraviolet light of 1000 nm, the film was heated in a hot air circulation drying oven at 160° C. for 1 hour to obtain a cured product. The opening diameter of the cured product pattern thus obtained was observed to evaluate the image forming properties after thermal curing.
[0176] ○: Maintain The opening shape allows for good opening.
[0177] ×: Unable to maintain The opening shape and opening diameter are significantly reduced.
[0178] (Determination of dielectric constant)
[0179] After peeling the second film from the laminated structure, the resin layer was laminated in such a manner that the resin layer was in contact with an electrolytic copper foil having a thickness of 18 μm (manufactured by Furukawa Electric Co., Ltd.) using CVP-300 manufactured by Nikko-Materials Co., Ltd., and the resin layer and the first film were laminated on the electrolytic copper foil. It should be noted that the lamination was carried out as follows: in a chamber at 70° C., under a vacuum pressure of 3 hPa, a vacuum time of 20 seconds, a pressurization time of 90 seconds, and a pressurization pressure of 0.4 MPa.
[0180] The resin layer laminated on the copper foil was exposed to light at 200 mJ / cm using EXP-2960 (light source: short arc lamp, parallel light exposure machine) manufactured by ORC MANUFACTURING CO., LTD. (ORC). 2 The entire surface is exposed with an accumulated light amount of and the first film is peeled off.
[0181] The resin layer (thickness 25 μm) of the laminated structure was further laminated on the resin layer (thickness 25 μm) from which the first film was peeled, and a resin layer with a thickness of 50 μm was formed on the copper foil. Then, the resin layer was exposed to light at 200 mJ / cm using EXP-2960 (light source; short arc lamp, parallel light exposure machine) manufactured by ORC MANUFACTURING CO., LTD. (ORC). 2The resin layer was exposed to the whole surface at a cumulative light dose of 1000 mJ / cm2 in a UV conveyor oven. The lamination was performed in a chamber at 70°C, under a vacuum pressure of 3 hPa, a vacuum time of 20 seconds, a pressurization time of 90 seconds, and a pressurization pressure of 0.4 MPa. The resin layer (thickness 50 μm) laminated on the copper foil was exposed to a cumulative light dose of 1000 mJ / cm2 in a UV conveyor oven. 2 After irradiating with ultraviolet rays under the conditions of , heating at 160° C. for 1 hour, a cured product was obtained.
[0182] Next, the copper foil having the solidified product was etched away with an etching solution composed of 340 g / l of copper chloride and 51.3 g / l of free hydrochloric acid, and then fully washed with water and dried to prepare a test piece formed of the solidified product with a thickness of 50 μm. It should be noted that the thickness of the test piece was measured by a micrometer in accordance with Japanese Industrial Standard B7502:2016.
[0183] The dielectric constant of the test piece prepared in this way was measured at 10 GHz using an SPDR dielectric resonator and a network analyzer (E5071C manufactured by Keysight Technologies).
[0184] Table 3: Examples
[0185] [Table 3]
[0186]
[0187] Table 4: Comparative Examples
[0188] [Table 4]
[0189] Evaluation Project Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Adhesion of the second film × 〇 × × Peelability of the second film 〇 × 〇 〇 Image formation after development and before thermal curing × 〇 △ △ Image formation after thermal curing - × × × Dielectric constant (10GHz) 32.8 27.0 27.4 27.0
[0190] The evaluation "-" of "image formation after heat curing" in Comparative Example 1 of Table 4 above means that the evaluation of "image formation after heat curing" was not performed. It should be noted that the reason for not performing the evaluation of "image formation after heat curing" is that the evaluation of "image formation after development and before heat curing" is "×", so there is no need to further perform the evaluation of "image formation after heat curing".
[0191] The laminated structures of Examples 1 to 15 are as follows: the adhesion and peelability between the resin layer and the second film are good, the image forming properties after development and before thermal curing and the image forming properties after thermal curing are both good, and a cured product showing a high dielectric constant can be obtained. On the other hand, the laminated structures of Comparative Examples 1 to 4 are as follows: it is difficult to simultaneously achieve the adhesion between all the resin layers and the second film, the image forming properties, and the high dielectric constant.
Claims
1. A laminated structure, characterized in that: The invention comprises a first film, a resin layer and a second film in sequence, The resin layer contains: (A) a carboxyl-containing resin, (B) a photocurable compound that does not contain a carboxyl group, (C) a photopolymerization initiator, (D) a perovskite compound, and (E) an epoxy resin. The content of the (D) perovskite compound is 55 to 85% by mass based on the solid content relative to the total mass of the resin layer. The (E) epoxy resin comprises a solid epoxy resin and a liquid epoxy resin, The content of the liquid epoxy resin is 150 to 1000 parts by mass based on solid content, relative to 100 parts by mass of the solid epoxy resin.
2. The laminated structure according to claim 1, characterized in that The content of the (D) perovskite compound is 70 to 85% by mass based on solid content relative to the total mass of the resin layer.
3. The laminated structure according to claim 1 or 2, characterized in that: The (D) perovskite compound is a divalent metal salt of titanic acid.
4. A solidified product, characterized in that: The laminate structure is obtained by curing the resin layer of the laminate structure according to claim 1.
5. An electronic component, characterized in that: A cured product according to claim 4.
Citation Information
Patent Citations
Process for preparing butyl-p-benzoylbenzoates
EP0000502A1
Prostaglandin analogues, process for their preparation and their use as medicaments
EP0000710A1
Process for the manufacture of hydrophilic fibres and filaments by the dry-jet wet spinning process
EP0000740A1
Method and apparatus for producing one-sidedly hot-galvanised sheets
EP0000860A1
Method and apparatus for demodulating a differential phase shift keying signal
EP0004822A1